CENTRAL MARINE FISHERIES RESEARCH STATION, MANDAPAM CAMP, S. INDIA - Mandapam, Central Mrine Fisheries Research Station (Indian Journal of Fisheries, 2016)
THE Central Marine Fisheries Research Station at Mandapam is one of the recently established Central Institutes of the Government of India under the Ministry of Food and Agriculture. The Institution was started in 1947 with temporary laboratory accommodation provided by the University of Madras. The headquarters at Mandapam was set up in 1949 when the buildings constructed originally as a naval hospital by the Defence Department during World War II, were acquired and converted into laboratories and temporary residences for the staff. Subsequently an aquarium was built and circulating sea-water facilities were provided for keeping marine organisms for study. A capital expenditure of about Rs. 6| lakhs has been incurred on the Station up to 1952-53. About a hundred acres of land adjoining the Institute has been acquired for expansion of the Station and for building permanent residences which will form a small self-contained colony. About ninety acres of land and the road leading to the site are being acquired at Mandapam on the Palk Bay side, for setting up an experimental Marine Fish Farm.